Regulation and drug development - Wardell, William M.; Lasagna, Louis (Washington : American Enterprise Institute for Public Policy Research, 1975)
Examines the regulations that have evolved from the therapeutic drugs and the impact of those regulations on new development and therapeutic practice, with special reference to the United States.
Includes bibliographical references.
oif 05/08/16
Loan
Keywords: Drug development; Drugs; Pharmaceutical industry; Pharmaceutical policy